Proton pump inhibitors as a possible cause of vitiligo: an in vivo and in vitro study. (15th November 2013) - Shin, J.M.; Lee, J.Y.; Lee, D.Y.; Yoon, T.Y.; Lee, J.C.; Lim, E.H.; Sohn, K.C.; Lee, Y.H.; Im, M.; Seo, Y.J.; Kim, C.D.; Lee, J.H.; et al.
Abstract Background Vitiligo is an acquired depigmentation disorder of melanocytes. Recently, some clinical reports have suggested that proton pump inhibitors (PPIs) may worsen vitiligo, but their effects on melanocytes have yet to be elucidated. Objective We investigated the effect of PPIs on melanogenesis in vivo and in vitro. Methods We examined the effect of PPIs on melanogenesis in B16 murine melanoma cells by measuring melanin content and tyrosinase (TYR) activity. TYR and tyrosinase‐related protein‐1 (TRP‐1) were monitored by western blotting. Finally, a PPI was applied to zebrafish embryos to investigate its in vivo effect on pigmentation. Results In agreement with our clinical experience of worsened vitiligo after PPI treatment, PPIs decreased both melanin content and TYR activity. Western blotting showed that PPIs decreased TYR and TRP‐1 protein levels. In the zebrafish test, PPIs inhibited body pigmentation in a dose‐dependent manner. Conclusion These results suggest that the functional inhibition of melanization by PPIs may induce or aggravate vitiligo lesions in genetically predisposed patients.